2020
DOI: 10.1128/aac.01881-19
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Clofazimine and TB47 Combination Activity against Mycobacterium abscessus Using a Bioluminescent Approach

Abstract: Mycobacterium abscessus is intrinsically resistant to most antimicrobial agents. The emerging infections caused by M. abscessus and the lack of effective treatment call for rapid attention. Here, we intended to construct a selectable marker-free autoluminescent M. abscessus strain (designated UAlMab) as a real-time reporter strain to facilitate the discovery of effective drugs and regimens for treating M. abscessus. The UAlMab strain was constructed using the dif/Xer recombinase system. In vitro and in vivo ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
1
14
1
Order By: Relevance
“…TB47 is an antimycobacterial candidate that has a good safety profile and ideal pharmacokinetic parameters (5,6), as well as good synergistic effects with other TB drugs (6,10). We used the Bangladesh regimen + TB47 (ALEZCT) from our previous study (11) as a positive control here, in which we further confirmed the highly synergistic activity of TB47 + CLF in shortening MDR-TB treatment duration to ≤ 5 months with no relapse in the murine TB model.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…TB47 is an antimycobacterial candidate that has a good safety profile and ideal pharmacokinetic parameters (5,6), as well as good synergistic effects with other TB drugs (6,10). We used the Bangladesh regimen + TB47 (ALEZCT) from our previous study (11) as a positive control here, in which we further confirmed the highly synergistic activity of TB47 + CLF in shortening MDR-TB treatment duration to ≤ 5 months with no relapse in the murine TB model.…”
Section: Discussionsupporting
confidence: 53%
“…We revealed that TB47 exerted high bactericidal and sterilizing activity and corresponding remarkable treatment-shortening effect in mice infected with Mycobacterium ulcerans which lacks cytochrome bd activity naturally (5,7). It has also shown a very good synergistic activity with clofazimine (CLF) against Mycobacterium abscessus and M. tuberculosis both in vitro and in vivo (10,11), and even played a remarkable role in shortening MDR-TB treatment duration from ≥ 9 to 5 months in a well-established murine model of TB (11). CLF competes with menaquinone and kills bacteria by generating lethal levels of reactive oxygen species (12), and regimens containing CLF and cytochrome bc 1 inhibitors or other electron transport chain-targeting drugs provide enhanced killing of both replicating and non-replicating M. tuberculosis (13)(14)(15), suggesting that dual or multiple targeting of the electron transport chain may be a novel approach to enhanced killing of mycobacteria (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…We initiated this study by determining the MICs of omadacycline and other antibiotics that have shown in vitro activity in prior studies, some of which are included in the current treatment recommendations for M. abscessus infection in humans ( 6 8 , 10 ). These include tigecycline, amikacin, clarithromycin, azithromycin, linezolid, moxifloxacin, rifabutin, vancomycin, teicoplanin, doripenem, imipenem, cefoxitin, cefdinir, ceftazidime, and amoxicillin, and those that have shown promise in recent studies, such as clofazimine and bedaquiline ( 17 , 36 45 ). These antibiotics represent a broad spectrum of antibiotic classes, including tetracycline, aminoglycoside, macrolide, fluoroquinolone, rifamycin, glycopeptide, β-lactam, phenazine, and diarylquinoline classes.…”
Section: Resultsmentioning
confidence: 99%
“…We selected the available proved oral drugs, rifampin, clarithromycin 7 and clofazimine 6 against BU first to test their sterilizing efficacy in combination with TB47. We expected that the long half-life clofazimine could show strong synergistic activity with TB47 as clofazimine had showed very good synergistic activity with TB47 against M. tuberculosis in vitro 15 and against M. abscessus both in vitro and in vivo in our recent studies 16 . The mean lgCFU per footpad were 5.89 ± 0.11 at Day 11 (one day after infection) and 6.55 ± 0.11 at Day 0, respectively.…”
Section: Resultsmentioning
confidence: 96%